(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The purpose of this study is to examine the perceptions of librarians on their leadership qualities. The respondents are 282 librarians from 20 public university libraries in Malaysia. The survey method is employed using a questionnaire to collect data. The librarian respondents are very positive on their own leadership qualities. In particular, they perceive their transformational leadership (mean=5.92) to be the highest, followed by emotional intelligence (mean=5.87), servant leadership (mean=5.77) and leadership skills (mean=5.60). Overall, the results show that librarians are very positive about their leadership qualities, however, they are moderately capable of understanding abstract ideas. In particular, leadership skill is positively and strongly correlated with servant leadership (r=0.795; p<0.01), followed by transformational leadership (r=0.794; p<0.01) and emotional intelligence (r=0.743; p<0.01). Similarly, the correlations between other pairs of leadership qualities’ dimensions are strong, positive and highly significant. This study is significant as it contributes to the body of knowledge in leadership qualities of university librarians. It benefits public university libraries, faculties, researchers and the Ministry of Education (MOE) and the nation.